2016
DOI: 10.21608/assjm.2016.103903
|View full text |Cite
|
Sign up to set email alerts
|

Growth, yield and yield components of wheat as affected by crop sequences, seeding rates and nitrogen fertilizer levels

Abstract: http://annagricmoshj.com Growth, yield and yield components of wheat as affected by crop sequences, seeding rates and nitrogen fertilizer levels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…in first and second season, respectively. These results are in agreement with those obtained by El -Mehy et al (2014) who reported that crop sequences had significant effect on, seed yield/fad, cereal units, total income and total net income of wheat. Legume as preceding crops for wheat gave significantly higheest grain yield and net income…”
Section: -Economic Returnsupporting
confidence: 93%
“…in first and second season, respectively. These results are in agreement with those obtained by El -Mehy et al (2014) who reported that crop sequences had significant effect on, seed yield/fad, cereal units, total income and total net income of wheat. Legume as preceding crops for wheat gave significantly higheest grain yield and net income…”
Section: -Economic Returnsupporting
confidence: 93%
“…Increasing nitrogen application is increasing cell division and elongation leads to an increase in plant height (Dogan and Bilgili, 2010). This finding was agreed with the result of (El-Mehy et al, 2016 andGad, 2018). Increased yield and yield components of wheat could be justified with logic that N availability satisfied wheat requirement for growth and development, which enabled the plant to produce a greater number of grains/spike (Chowdhury et al, 2018).…”
Section: Vii-economic Evaluationsupporting
confidence: 73%
“…The conventional monoculture of maize, maize + soybean (intercropping) had a significant advantage in yield, economy, land utilization ratio and reducing soil nitrate nitrogen (N) accumulation, as well as a better residual effect on the subsequent wheat (Zhang et al, 2015). Also, inclusion of three crops (faham berseem, pea, fodder maize) in the Egyptian crop structure will certainly increase the cereal units, net incomes, and cropping index (CI) of cropping sequence compared to maize-wheat prevailing cropping sequence (El-Mehy et al, 2016). The sequence of corn-clover-wheat produced higher grain and straw yield when compared to the sequence of corn-fallow-wheat (Gad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Fahl berseem as preceding crops for wheat gave significantly higher grain yield compared with fodder maize. Similarly, the highest grain yield and net income after fahl berseem, (2.959, 2.980 ton and 5422, 5414 LE) in the 1 st and 2 nd seasons, respectively (El-Mehy et al, 2014).…”
Section: Introductionmentioning
confidence: 88%